Frequency of Various Post Polio Deformities in Lower Limbs and There Correction with Conventional Procedure at Mercy Teaching Hospital Peshawar (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To evaluate the outcome of various post polio deformities in lower limbs and their correction by conventional surgery.Study design: Descriptive case seriesPlace of Study and duration: Orthopedic department, Mercy Teaching Hospital, Peshawar Medical College, Peshawar, KPK, Pakistan. Study carried out from January 2008 to December 2012.Methodology: It is a study that included all patients who needed surgical intervention for Post polio lower limb deformities. The data of all the patients with deformity and procedure was entered on a Performa and the results analyzed with SPSS version 14.Results: There were 30 patients with 12 (40%) males and 18 (60%) females. Mean age was 16.73 years (range 08-30 years). Among 30 patient 24(80%) had ankle and foot deformity, 3(10%) patient had knee deformity, 2(6.67%) had deformity of hip joint and 1 (3.33%) with leg length discrepancy. Among ankle and foot deformities 7(29.17%) had Equinovarus deformity, 5 (20.82% )had clawing of great toe, 4 (16.67% ) had cavus deformity at midfoot level along with clawing of toes ,3(12.5% ) Equinovalgus deformity, 2(8.33%) cavovarus ,1(4.17%) had cavovalgus,1(4.17%) calcaneovalgus and 1(4.17%)with flail foot. In knee all three deformity were fixed flexion deformity of 30 degree. In hip there was abductor contracture in 2 patients.Conclusion: Conventional methods are less cumbersome, economical, need less instrumentation and usually give good results. Key words: Polio, Post poliomyelitis Syndrome, Foot, Ankle, Knee, Hip, Deformities.